Magnetisation transfer effects at ultra high field MRI - Shah, Simon Michael (2017)
Increased signal to noise ratio in ultra high field Magnetic Resonance Imaging (MRI) has allowed the development of quantitative imaging techniques and new contrast mechanisms, such as Chemical Exchange Saturation Transfer (CEST) to be probed. The development of CEST contrast imaging has involved overcoming a number of technical challenges associated with ultra high field MRI. The B1 transmit field was, and still is, a major challenge. Presented in this thesis, the B1 transmit field in regions of low B1 are improved with the use of dielectric pads and a simulation study shows that the overall B1 transmit field homogeneity is significantly improved when multi-transmit slice-selective RF spokes pulse sequences are used. Multiple methods have been developed to quantify the chemical exchange from slow exchanging proton pools seen in CEST contrast imaging. However, magnetisation transfer (MT) from the macromolecular bound pool contaminates current quantification methods, and presented in this thesis is a method whereby the CEST and MT are simultaneously saturated using dual frequency saturation pulses, allowing the CEST contrast in z-spectra to be separated from the MT and to enhance visualisation of the CEST effects. Despite the considerable interest in CEST, only one study has probed the CEST effects in blood, and interestingly high levels of CEST signals can be observed from the superior sagittal sinus. To investigate these effects, z-spectra from ex vivo blood samples considering the effects of oxygenation, haematocrit levels and cell structure were quantified. Quantification shows that the main source of the CEST signals was from the cells within the blood.